2018
DOI: 10.14710/jitaa.43.1.1-8
|View full text |Cite
|
Sign up to set email alerts
|

Genotype analysis of partial growth hormone gene (GH891│MspI) in Pesisir cattle and Simmental-Pesisir crossbred cattle

Abstract: ABSTRAKGen Growth Hormone (GH) merupakan sebuah gen yang mengontrol sintesis hormon pertumbuhan dan berperan dalam metabolisme tubuh. Identifikasi polimorfisme suatu gen penting dilakukan untuk memperoleh informasi awal dalam mengetahui penanda genetik yang berhubungan dengan sifat-sifat ekonomis yang diinginkan. Pemetaan genetik sangat penting dalam proses seleksi. Sapi Pesisir adalah salah satu sapi lokal Indonesia yang ditemukan di Sumatera Barat dan sangat adatif terhadap lingkungan setempat. Penelitian in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Results of the present work are in agreement with those published by Dybus et al (2002) in Polish Black-and-White cattle and by Zhou et al (2006) in China Holstein cows. However, Hartatik et al (2018) reported a higher frequency of the MspI(+/−) genotype than the MspI(−/−) and MspI(+/+) genotypes in Pesisir cattle and cross breeds, in addition to the fact that MspI(−) allele was more frequent than the MspI(+) allele (0.533 vs. 0.467).…”
Section: Discussionmentioning
confidence: 88%
“…Results of the present work are in agreement with those published by Dybus et al (2002) in Polish Black-and-White cattle and by Zhou et al (2006) in China Holstein cows. However, Hartatik et al (2018) reported a higher frequency of the MspI(+/−) genotype than the MspI(−/−) and MspI(+/+) genotypes in Pesisir cattle and cross breeds, in addition to the fact that MspI(−) allele was more frequent than the MspI(+) allele (0.533 vs. 0.467).…”
Section: Discussionmentioning
confidence: 88%
“…Hardy-Weinberg Equilibrium was calcuLated according to Warwick et al (1990). (Putra et al 2016;Yurnalis et al 2017;Putra et al 2018;Hartatik et al 2018) associating with growth and economic traits performance. The allelic and genotypic frequencies of the GH/AluI, GH/MboII, PIT1/HindfI and IGF1/MspI polymorphisms were estimated by the genotyping of 175 individuals from Pesisir cattle using PCR-RFLP technique.…”
Section: Discussionmentioning
confidence: 99%
“…However, distribution of these polymorphisms in the zebu cattle remains unclear. Putra et al (2016); Yurnalis et al (2017); Putra et al (2018); Hartatik et al (2018) reported that genetic analyses of local breeds of Indonesian native cattle showed gene-flow of banteng (Bos javanicus), Southeast Asian wild cattle, into some of these breeds. In the present study, we found that the polymorphisms of GH/AluI, GH/MboII, PIT1/HindfI and IGF1/MspI genes reported in Indonesian native cattle were also observed in the population of Pesisir cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Pighin et al (2016) stated that beef remains a popular choice due to its complete nutritional profile, including protein and fat, and its appealing taste. Pesisir cattle, a local Indonesian bread, exhibit high adaptability to low-quality feed and resistance to various diseases and parasites (Hartatik et al, 2018). They demonstrate superior heat tolerance in hot environments compared to the simmental and ongole crossbreeds (Yetmaneli et al, 2023).…”
Section: Introductionmentioning
confidence: 99%